Estetika Macan Kurung sebagai Sumber Potensi Peningkatan Ekonomi Masyarakat dan Pelestarian Seni Ukir di Jepara - Habib Hasan Abdi Masabdi (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
Regional culture is one of the things that become assets and is also used as an aspect of the identity of a community group that shows a form of manifestation of intellectual community. Art is one of the elements of culture that is the embodiment of the tastes of the nation's people related to beauty aspects or aesthetics. The city of Jepara is one of the cities in Central Java which is known to the world community as the City of Carving. Jepara’s carving art has developed over the centuries and this has positive impacts on the variety of creative designs and the quality of the sculptures. Jepara’s sculpture called